A Persian Alice in Disability Literature Wonderland: Disability Studies in Iran - Goodrich, Negin H. (Disability Studies Quarterly, 2014)
Exploring major requisites to establish an Iranian disability studies, the aim of this study is to determine how a local literature of disability can be formed in Iran, as well as how the Iranian and global disability studies might interchange disability knowledge. In an analysis of the responses to a qualitative questionnaire, three themes emerged: rudimentary resources, disability literature, and political prerequisites. Accordingly, human and financial resources, a bank of Farsi and English literature on disability, as well as developing academic relations between Iranian and international disability scholars (as an outcome of improving the Iran-USA political affairs) are essential to form a local disability studies in Iran and to engage it in the global discussions of disability studies. Keywords: disability, global disability studies, Iran